2016
DOI: 10.1038/labinvest.2016.55
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the vitamin D receptor selectively interferes with calcineurin-mediated inflammation: a clinical evaluation in the abdominal aortic aneurysm

Abstract: In vitro and in vivo studies attribute potent immune regulatory properties to the vitamin D receptor (VDR). Yet, it is unclear to what extend these observations translate to the clinical context of (vascular) inflammation. This clinical study evaluates the potential of a VDR agonist to quench vascular inflammation. Patients scheduled for open abdominal aneurysm repair received paricalcitol 1 μg daily during 2-4 weeks before repair. Results were compared with matched controls. Evaluation in a parallel group sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 35 publications
(39 reference statements)
0
14
0
Order By: Relevance
“…A brief intervention study with paricalcitol two to 4 weeks prior to scheduled abdominal aneurysm repair resulted in a significant reduction in CD4+ T‐helper cells, and reduction in CD3+ T cells, as well as reduction in IL‐2, IL‐4, and IL‐10 in the aneurysm wall samples . These findings support that paricalcitol as a vitamin D receptor agonist may have effects on local inflammation.…”
Section: Discussionmentioning
confidence: 54%
“…A brief intervention study with paricalcitol two to 4 weeks prior to scheduled abdominal aneurysm repair resulted in a significant reduction in CD4+ T‐helper cells, and reduction in CD3+ T cells, as well as reduction in IL‐2, IL‐4, and IL‐10 in the aneurysm wall samples . These findings support that paricalcitol as a vitamin D receptor agonist may have effects on local inflammation.…”
Section: Discussionmentioning
confidence: 54%
“…Furthermore, the anti-inflammatory effect of vitamin D by reducing the expression of inflammatory mediators, CD4+ T-helper cells, and cytokines IL-2, IL-4, and IL-10 with paricalcitol and reduction in the local inflammation in AAA patients suggest the therapeutic role of vitamin D in arterial aneurysms. The anti-inflammatory action of vitamin D was suggested to be mediated by an effect on calcineurin-mediated responses [116](Table 1). Further, a meta-analysis comprising six case-control studies assessing 6,418 patients with PAD suggests the association of low levels of circulating vitamin D with PAD and with chronic limb ischemia [17].…”
Section: Vascular Diseasementioning
confidence: 99%
“…Previous studies indicated a strong association between hypovitaminosis D and the presence and extend of arterial diseases, regardless of traditional cardiovascular risk factors and different cardiovascular pathologies, from coronary artery disease, to peripheral artery disease and aneurysms [17]. The association with the presence and the extent of aneurysms has also been observed regardless of atherosclerosis which is considered one leading cause of aneurysm formation, thus suggesting a potential direct effect of vitamin D action on artery walls [911]. In this regard, vitamin D receptor is expressed both on endothelial as well as on smooth muscle cells where vitamin D can control cellular survival and local inflammation by preventing macrophage infiltration and the consequent production of proinflammatory and detrimental mediators [30, 31].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggested the existence of an inverse relationship between 25OHD levels and the presence and size of aortic aneurysms and thoracic aortic dilatations [911]. The underlying mechanisms explaining these associations are not fully understood but probably deal with processes which may be affected by hypovitaminosis D, such as wall vessel inflammation, endothelial dysfunction, and artery wall integrity.…”
Section: Introductionmentioning
confidence: 99%